DESIGNING STUDENTS WORKSHEET BASED ON MEAS OF THREE VARIABLES LINEAR EQUATION SYSTEM MATERIAL - R Wulandari; C Hiltrimartin; Darmawijoyo Darmawijoyo; Indaryanti Indaryanti (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to produce the student worksheet designs based on MEAs. In designing it uses the development of ADDIE (Analysis, Design, Development, Implementation and Evaluation) models. This study only steps were taken to analyze and design. In the analysis phase, an assessment of basic competencies is carried out. Next, it composes indicators based on basic competencies. Beside that, researchers also study the MEAs approach. After the first step, proceed with compiling student worksheet.